Contribution of Islamic Law to Legal Development in Indonesia - Damayanti, Aula (Faculty of Sharia, IAIN Metro, 2022)
The legal system used in Indonesia is a civil law legal system, namely a codified or written legal system. The contribution of Islamic law in Indonesia is the development, guidance and application of Islamic law as positive law in the context of efforts to develop and foster national law. The Role of Islamic Law in Legal Development in Indonesia. The dynamic character of Islamic law must be developed to support the development of national law in the realm of legal development in Indonesia. It is necessary to provide limits on the scope of areas of life covered by Islamic law in the context of developing national law. These limitations in the field of Islamic law must be followed up by Islamic legal experts. The cultivation of Islamic law is carried out with an effort to formulate principles for Islamic legal decision making that better reflect current needs accompanied by proportional humanitarian considerations. During the period of Indonesian independence, Islamic law, Western law and customary law both became materials for the development of national legal unification.